2012
DOI: 10.1177/0892020611427068
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Early Years leadership preparation: a comparison between early and experienced Early Years practitioners in England

Abstract: Leadership has been under-researched in the Early Years (EY) sector of primary schools in England, especially in leading change for professional development. The aim of this paper is to theorise what the leadership culture for EY practitioners looks like, and how Initial Teacher Training providers and schools are preparing practitioners for leadership. Using case studies of EY practitioners in different stages of their career in primary schools, we offer an insight into their preparedness for leadership in EY,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
1
8
0
1
Order By: Relevance
“…Consistent with the literature (Mistry & Sood, 2012), our findings indicated that although early childhood educators acknowledged the importance of leadership skills, their perceptions of leadership were not yet at a sophisticated level.…”
Section: Perceptions Of Leadershipsupporting
confidence: 80%
See 1 more Smart Citation
“…Consistent with the literature (Mistry & Sood, 2012), our findings indicated that although early childhood educators acknowledged the importance of leadership skills, their perceptions of leadership were not yet at a sophisticated level.…”
Section: Perceptions Of Leadershipsupporting
confidence: 80%
“…Mistry & Sood (2012) cite insufficient training as a primary reason for the reluctance of early childhood professionals to adopt leadership roles. This is consistent with Thornton's (2010) belief that it is highly unlikely that early childhood professionals will have received formal preparation as part of their undergraduate studies to take on a leadership role.…”
Section: Introductionmentioning
confidence: 99%
“…Training institutions, such as universities, are accountable for the quality of training and the development of potential leaders (Clark, 2012;Mistry & Sood, 2012). The exclusion of graduates taking on leadership roles until their final career stage may signal to training institutions that leadership in undergraduate courses is not as important.…”
Section: Evaluation Discussion and Conclusionmentioning
confidence: 99%
“…Leadership within ECE is a complex task (Mistry & Sood, 2012) and may include leadership of people, practice and pedagogy. Practitioners have to meet multiple demands and deal with complex tasks that involve children, other practitioners and parents (Miller, 2008).…”
Section: Leadership As a Complex And Socially Situated Activitymentioning
confidence: 99%